2020
DOI: 10.1088/2631-8695/ab9bf0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the impact of the gate work-function and biases on the sensing metrics of TFET based biosensors

Abstract: In this work, we examined the impact of gate work-function and back-gate bias to enhance sensing metrics of a Dielectric Modulated (DM) p-type Tunnel Field Effect Transistor (p-TFET) based biosensor. The sensing metrics, namely Sensitivity (S) and Selectivity (ΔS) are considerably improved by using a lower value of gate work-function and positive back gate voltages. It is shown that by appropriate selection of gate work-function and back gate bias, Band-to-Band Tunneling (BTBT) of carriers is reduced and a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In Figure 9 a,b, we show the comparison of the DM-LTFET metrics with previously published papers. It can be clearly seen from Figure 9 a that, compared with previously published papers [ 16 , 17 , 18 , 20 , 26 ] (which have double gates), the DM-LTFET could simultaneously have a larger on-state current and I on / I off sensitivity. At the same time, it can be obviously seen from Figure 9 b that the current sensitivity and sub-threshold swing sensitivity of the proposed structure were higher than those of the past published papers [ 16 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In Figure 9 a,b, we show the comparison of the DM-LTFET metrics with previously published papers. It can be clearly seen from Figure 9 a that, compared with previously published papers [ 16 , 17 , 18 , 20 , 26 ] (which have double gates), the DM-LTFET could simultaneously have a larger on-state current and I on / I off sensitivity. At the same time, it can be obviously seen from Figure 9 b that the current sensitivity and sub-threshold swing sensitivity of the proposed structure were higher than those of the past published papers [ 16 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 77%
“…Due to its low cost and easy operation, dielectric modulation is applied in biosensors [ 11 , 12 , 13 , 14 ]. Therefore, sensors made using dielectric modulation based on a TFET have been studied by many scholars [ 15 , 16 , 17 , 18 ]. In 2016, Kanungo et al studied the influence of silicon germanium (SiGe) sources and n+-pocket-doped channels on dielectric modulation sensors.…”
Section: Introductionmentioning
confidence: 99%
“…FETs were also recently utilized to diagnose the highly contagious COVID-19 illness due to the corona virus [4]. Various research groups [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] have reported on the development of dielctrically modulated FET-based biosensors. Biosensors produced using FETs may be fabricated using either inorganic or organic semiconducting materials [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel FET (TFET) is one of the emerging devices which overwriting the conventional MOSFET as a biosensor due to its band to band tunneling mechanism. It is overcoming the issue of sub-60 mV/decade subthreshold swing for MOSFET at room temperature and also TFET emerging as a promising candidate for various sensing application [11][12][13][14][15][16]. Dielectric modulated TFET with various structures [6][7][8][9][11][12][13][14][15][16] have been reported since last decades which is able to produce higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is overcoming the issue of sub-60 mV/decade subthreshold swing for MOSFET at room temperature and also TFET emerging as a promising candidate for various sensing application [11][12][13][14][15][16]. Dielectric modulated TFET with various structures [6][7][8][9][11][12][13][14][15][16] have been reported since last decades which is able to produce higher sensitivity. The higher sensitivity in biosensors means Fig.…”
Section: Introductionmentioning
confidence: 99%